2022
DOI: 10.1007/s00415-022-11497-x
|View full text |Cite
|
Sign up to set email alerts
|

Conceptualization, use, and outcomes associated with compassion in the care of people with multiple sclerosis: a scoping review

Abstract: Objective Compassion is widely regarded as an important component of high-quality healthcare. However, its conceptualization, use, and associated outcomes in the care of people with multiple sclerosis (PwMS) have not been synthesized. The aim of this review is to scope the peer reviewed academic literature on the conceptualization, use, and outcomes associated with compassion in the care of PwMS. Methods Studies were eligible for inclusion if reporting pri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 94 publications
0
3
0
Order By: Relevance
“…Several scoping reviews on compassion within the healthcare context have noted that compassion is often studied in healthcare providers more frequently than in patients ( Sinclair et al, 2016 ; Malenfant et al, 2022 ; Simpson et al, 2022 ). However, within the childhood-onset disability population, none of the reviewed studies described the interpersonal qualities or skills that define compassionate pediatric healthcare providers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several scoping reviews on compassion within the healthcare context have noted that compassion is often studied in healthcare providers more frequently than in patients ( Sinclair et al, 2016 ; Malenfant et al, 2022 ; Simpson et al, 2022 ). However, within the childhood-onset disability population, none of the reviewed studies described the interpersonal qualities or skills that define compassionate pediatric healthcare providers.…”
Section: Discussionmentioning
confidence: 99%
“…Compassion is often included in the competency frameworks and codes of ethics of professional healthcare organizations and is a crucial component of providing quality healthcare ( Sinclair et al, 2016 ; Malenfant et al, 2022 ; Simpson et al, 2022 ). Several physician behaviors identified by patients as important to providing compassion within healthcare interactions include: (1) listening and paying attention to the patient; (2) respecting preferences (i.e., physicians are culturally competent, respect the patient’s preferences and ensure patients are actively involved in healthcare decisions); (3) continuity of care (i.e., long-term management of chronic conditions with a physician); (4) genuine understanding (i.e., seeking to understand the patient’s situation and symptoms to attempt to identify a cause); (5) following-up on patient test results; (6) body language (i.e., not speaking over a patient, physician moves their chair to face patient, and explaining diagnosis in a manner the patient will understand); and (7) counseling and advocacy (i.e., being non-judgmental toward concerns related to mental health, chronic illness and diagnoses with somatic complaints, showing sensitivity, and providing counseling and advocacy related to these concerns) ( Baguley et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Ferrari et al’s (2019) meta-analysis found that self-compassion interventions had beneficial effects across 11 psychosocial outcomes, including eating behavior, rumination, self-compassion, stress, depression, MI, self-criticism, and anxiety. Further meta-analyses reported that self-compassion benefits the psychological well-being of diverse populations, including people with multiple sclerosis (Simpson et al, 2023), sexual and gender minorities (Helminen et al, 2023), patients with breast cancer (Fan et al, 2023), Asian communities (Kariyawasam et al, 2023), those who are self-critical (Wakelin et al, 2022), and those with body image concerns (Turk & Waller, 2020).…”
Section: The Self-compassion Constructmentioning
confidence: 99%